Preclinical Characterization of Antioxidant Quinolyl Nitrone QN23 as a New Candidate for the Treatment of Ischemic Stroke - Emma Martínez-Alonso; Alejandro Escobar-Peso; Alicia Aliena-Valero; Germán Torregrosa; Mourad Chioua; Rocío Fernández-Serra; Daniel González-Nieto; Youness Ouahid; Juan B. Salom; Jaime Masjuan; José Marco-Contelles; Alberto Alcázar (MDPI AG, 2022)
Nitrones are encouraging drug candidates for the treatment of oxidative stress-driven diseases such as acute ischemic stroke (AIS). In a previous study, we found a promising quinolylnitrone, QN23, which exerted a neuroprotective effect in neuronal cell cultures subjected to oxygen-glucose deprivation and in experimental models of cerebral ischemia. In this paper, we update the biological and pharmacological characterization of QN23. We describe the suitability of intravenous administration of QN23 to induce neuroprotection in transitory four-vessel occlusion (4VO) and middle cerebral artery occlusion (tMCAO) experimental models of brain ischemia by assessing neuronal death, apoptosis induction, and infarct area, as well as neurofunctional outcomes. QN23 significantly decreased the neuronal death and apoptosis induced by the ischemic episode in a dose-dependent manner and showed a therapeutic effect when administered up to 3 h after post-ischemic reperfusion onset, effects that remained 11 weeks after the ischemic episode. In addition, QN23 significantly reduced infarct volume, thus recovering the motor function in a tMCAO model. Remarkably, we assessed the antioxidant activity of QN23 in vivo using dihydroethidium as a molecular probe for radical species. Finally, we describe QN23 pharmacokinetic parameters. All these results pointing to QN23 as an interesting and promising preclinical candidate for the treatment of AIS.